Endocrine Hypertension Underlying Mechanisms and Therapy - Koch, Christian A.; Chrousos, George P. (Contemporary Endocrinology, 2013)
The prevalence of hypertension is almost three times as high as that of diabetes mellitus type 2, with both conditions being major risk factors for stroke, ischemic heart disease, cardiac arrhythmias, and heart failure.  The exact prevalence of hypertension related to hormonal derangements (endocrine hypertension) is not known but estimated to affect less than 15% of hypertensive patients.  Recent scientific discoveries have increased the understanding of the pathophysiologic mechanisms of hypertension.  In Endocrine Hypertension, a renowned panel of experts provides a comprehensive, state-of-the-art overview of this disorder, discussing when to assign an endocrine cause in one of  many conditions that may present with hypertension.   The first part of Endocrine Hypertension is dedicated to adrenal causes.  The second part of the volume concerns potential nonadrenal causes of hypertension, such as growth hormone excess or deficiency, primary hyperparathyroidism, vitamin D deficiency, testosterone deficiency, insulin resistance, obesity-associated hypertension, and the role of central mineralocorticoid receptors and cardiovascular disease. An important contribution to the literature, Endocrine Hypertension is an indispensable reference not only for endocrinologists, diabetologists, and adrenal investigators, but also for translational scientists and clinicians from cardiology, internal medicine, pediatrics, family medicine, geriatrics, urology, and reproductive medicine / gynecology.